Metabolic Checkpoints in Differentiation of Helper T Cells in Tissue Inflammation - Roy, Suyasha; Rizvi, Zaigham Abbas; Awasthi, Amit (Frontiers in Immunology, 2019)
Naïve CD4+ T cell differentiate into effector and regulatory subsets of T cells in various pathophysiological conditions modulating tissue inflammation in autoimmune diseases. While cytokines play a key role in differentiation of T cells, metabolites and metabolic pathways profoundly affect T cell fate and their functions. Emerging literature suggests that interplay between metabolic pathways potentiate T cell differentiation and functions during inflammation and autoimmune diseases. Metabolic pathways, essential for the differentiation and functions of T helper cell subsets, are regulated by cytokines, nutrients, growth factors, local oxygen levels, co-activation receptors and metabolites. Dysregulation of metabolic pathways alters metabolic regulators in T cells, and therefore affect tissue inflammation in autoimmune and allergic diseases. Understanding the modulation of metabolic pathways during T cells differentiation may potentially lead to a therapeutic strategy for immune-modulation in autoimmune and allergic diseases. In this review, we summarize the role of metabolic checkpoints and their crosstalk with different master transcription factors and signalling molecules of different T helper subsets, which may potentially unravel novel therapeutic interventions for tissue inflammation and autoimmune disorders.